Clinical Profile of Ectopic Pregnancy in Karnali Province Hospital, Surkhet Nepal - Dhakal, Keshar Bahadur; Khadka, Damber; Dhakal Rai, Sulochana; Bhandari, Saroj; Dhakal, Astha (Journal of Karnali Academy of Health Sciences, 2021)
Background: Ectopic pregnancy (EP) is one of the major causes of preventable maternal death in the first trimester of pregnancy. The incidence of EP varies between 1 – 2 % worldwide. The main objective of this study is to explore the incidence, predisposing factors, clinical presentations, and approaches for the management of EP in Karnali Province Hospital (KPH), Nepal.Methods: This is a retrospective study carried out in KPH between 14 April 2013 to 13 April 2018. Data were extracted from patients’ admission files, discharge registers, and operation theatre (OT) notes. Data were then analyzed by SPSS version 26. Percentage, frequency, and interquartile range (IQR) were calculated and displayed in the tables and figures. Ethical approval was granted from hospital authority prior to the study.Results: The incidence of ectopic pregnancy is found to be 0.33% in our study. The median age of the patient was 28 years and the median gestational age for ectopic was 8 weeks. The majority of patients were from Surkhet (70%) and Brahmin/Chhetri ethnicity (52.6%). Most cases were multigravida (80.7%). In this study, most the patients presented with abdominal pain (96.4%), amenorrhoea (96.4%), and vaginal bleeding (87.7%). The main predisposing factors of EP were a history of previous abortion (35.10%) and pelvic inflammatory diseases (PID) (21.10%). Most of the patients (87.7%) had undergone surgery for the treatment of EP.Conclusion: In our study, the incidence of ectopic pregnancy is comparatively very low (0.33%). EP is found most common in multigravida and up to 10 weeks gestation of pregnancy. Previous abortion and PID were the most common predisposing factors. The main clinical presentations of EP were abdominal pain, amenorrhoea, and vaginal bleeding. Laparotomy was the main mode of treatment for EP in KPH.